PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP MINAT BELAJAR SISWA SMP - Zakiatun Nafisah Zainafa; Didit Darmawan; Rahayu Mardikaningsih (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Low student interest in learning Islamic Religious Education (PAI) can affect the effectiveness of the learning process. The use of technology-based learning media has become an alternative approach to creating more engaging and interactive learning experiences. This study aims to analyze the influence of technology-based learning media on students’ learning interest in PAI at the junior high school level. The study employed a Systematic Literature Review (SLR) method through the stages of identification, selection, evaluation, and synthesis of relevant literature. Data were collected from articles indexed in Google Scholar, Garuda, Scopus, and DOAJ published between 2021 and 2026, with inclusion criteria focusing on technology-based learning media in PAI instruction at the junior high school level and the availability of full-text articles. A total of 30 articles met the selection criteria and were analyzed using a descriptive qualitative approach. The novelty of this study lies in synthesizing recent findings on the use of technology-based learning media in junior high school PAI learning during the 2021–2026 period. The findings indicate that instructional videos, interactive multimedia, and digital platforms enhance students’ attention, interest, motivation, and active participation. Most of the reviewed studies reported an increase in students’ learning interest following the implementation of technology-based learning media. Therefore, the integration of technology in PAI learning contributes positively to improving students’ learning interest. ABSTRAK Rendahnya minat belajar siswa pada mata pelajaran Pendidikan Agama Islam (PAI) dapat memengaruhi keberhasilan proses pembelajaran. Pemanfaatan media pembelajaran berbasis teknologi menjadi salah satu alternatif untuk menciptakan pembelajaran yang lebih menarik dan interaktif. Penelitian ini bertujuan menganalisis pengaruh penggunaan media pembelajaran berbasis teknologi terhadap minat belajar siswa pada mata pelajaran PAI di tingkat SMP. Penelitian menggunakan metode Systematic Literature Review (SLR) melalui tahapan identifikasi, seleksi, evaluasi, dan sintesis literatur. Sumber data diperoleh dari artikel yang terindeks pada Google Scholar, Garuda, Scopus, dan DOAJ periode 2021–2026 dengan kriteria artikel membahas media pembelajaran berbasis teknologi pada pembelajaran PAI di tingkat SMP dan tersedia dalam teks lengkap. Sebanyak 30 artikel memenuhi kriteria dan dianalisis secara deskriptif kualitatif. Kebaruan penelitian ini terletak pada sintesis temuan terkini mengenai pemanfaatan media pembelajaran berbasis teknologi dalam pembelajaran PAI tingkat SMP selama periode 2021–2026. Hasil kajian menunjukkan bahwa penggunaan video pembelajaran, multimedia interaktif, dan platform digital mampu meningkatkan perhatian, ketertarikan, motivasi, serta partisipasi aktif siswa. Sebagian besar literatur menunjukkan adanya peningkatan minat belajar setelah penerapan media pembelajaran berbasis teknologi. Dengan demikian, integrasi teknologi dalam pembelajaran PAI berkontribusi positif terhadap peningkatan minat belajar siswa.